EFEKTIVITAS PELAKSANAAN DIKLAT PRAJABATAN PADA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN KABUPATEN MAMASA - Israwati Israwati; Ahmad Saleh (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
This study aims to determine the effectiveness of the implementation of Pre-service Training at the Mamasa Regency Personnel Education and Training Agency and the factors that influence it. Data collected through observation, interviews, and documentation. Qualitatively analyzed with interactive patterns. The results show that the implementation of Pre-service Training is not yet effective. The influencing factors are widyaswara, infrastructure and time of implementation. While other factors such as training participants, curriculum and training process are considered quite effective. Not all Widyaswara who teach at Pre-service Training are competent according to their fields, with material that is difficult for participants to understand so that it affects the success of the training. Existing facilities and infrastructure are still not conducive, so that participants feel less comfortable.